A conformational landscape for alginate secretion across the outer membrane of Pseudomonas aeruginosa - CAFFREY, MARTIN (My University, 2014)
The exopolysaccharide alginate is an important component of biofilms produced by Pseudomonas aeruginosa , a major pathogen that contributes to the demise of cystic fibrosis patients. Alginate exits the cell via the outer membrane porin AlgE. X-ray structures of several AlgE crystal forms are reported here. Whilst all share a common -barrel constitu- tion, they differ in the degree to which loops L2 and T8 are ordered. L2 and T8 have been identified as an extracellular gate (E-gate) and a periplasmic gate (P-gate), respectively, that reside on either side of an alginate-selectivity pore located midway through AlgE. Passage of alginate across the membrane is proposed to be regulated by the sequential opening and closing of the two gates. In one crystal form, the selectivity pore contains a bound citrate. Because citrate mimics the uronate monomers of alginate, its location is taken to highlight a route through AlgE taken by alginate as it crosses the pore. Docking and molecular-dynamics simula- tions support and extend the proposed transport mechanism. Specifically, the P-gate and E-gate are flexible and move between open and closed states. Citrate can leave the selectivity pore bidirectionally. Alginate docks stably in a linear conformation through the open pore. To translate across the pore, a force is required that presumably is provided by the alginate-synthesis machinery. Accessing the open pore is facilitated by complex formation between AlgE and the periplasmic protein AlgK. Alginate can thread through a continuous pore in the complex, suggesting that AlgK pre-orients newly synthesized exopolysaccharide for delivery to AlgE.
PUBLISHED
Keywords: Pseudomonas aeruginosa; Pseudomonas aeruginosa